GASIFICATION STUDY OF SARAWAK COALS - Nor Fadzilah Othman; Mohd Hariffin Bosrooh (Universitas Gadjah Mada, 2008)
Thermogravimetry (TG) has been applied in a preliminary investigation, to the gasification of two low rank Sarawak coals. The coal samples, about 10 mg were investigated within the temperature range 30–900°C at different heating rate of 10, 20 and 30°C min-1, under a synthetic air atmosphere for the gasification study. The kinetic parameters were determined using Arrhenius type reaction model assuming a first-order reaction. The reactivity, RT values are fitted with Arrhenius equation at r2 = 0.83 - 0.98 for MP coal, while the RT values for MB coal are fitted with the Arrhenius equation at r2 = 0.99. The activation energy, EA for MP coal are in the range of 3.7 -4.7 kJ mol-1 and for MB coal are 7.6 - 25.6 kJ mol-1 at 3 different heating rates.